Adaptive Interference Mitigation in GNSS - Wu, Renbiao; Wang, Wenyi; Lu, Dan.; Wang, Lu.; Jia, Qiongqiong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book introduces readers to adaptive interference mitigation techniques based on multiple antennas for global navigation satellite systems (GNSS) in the time, domain, spatial and spatial-temporal domains. As the performance of GNSS can easily be impacted by various intentional and unintentional interferences, the book explores in detail various types of interference, including jamming , high dynamic jamming, spoofing, multipath and pulsed interference. It offers a valuable reference work for graduate students and engineers in the field of satellite navigation and signal processing.
Principles of Satellite Navigation System -- Jamming Suppression -- High-Dynamic Jamming Suppression -- Spoofing Suppression -- Multipath Interference Suppression -- Pulsed Interference Suppression.
Keywords: Aerospace engineering; Astronautics; Signal processing; Telecommunication; Aerospace Technology and Astronautics; Signal, Speech and Image Processing; Communications Engineering, Networks